Living Labour: The entelechy of Capital - García Palacios, Moisés (Logos. Anales del Seminario de Metafísica, 2018)
Living labor is not an economic category, but is part of the human practical activity that appears from the origin of human life. Starting from an ontological analysis of labor activity, we find that living labor is the simple category on which the rest of economic categories are articulated. However, in the capitalist system of production, living labor is turned into the essential determination of the capital in its process of valorization. In this way, while the active and the subjective is transformed into a dead objectivity for the producers themselves, capital reaches its full perfection with it: surplus value. The philosophical perspective must allow us to analyze, to show and to specify the intimate relations that are established between capital and labor, as well as the metamorphosis and transformations that living labor must undergo to become an entelechy of capital, namely, the transit from the living to the dead.